Assessment of Risk Score for Developing Type 2 Diabetes Mellitus among Bangladeshi Adults Using Indian Diabetes Risk Score (Delta Medical College Journal, 2024)
Background: Different studies support the utilization of risk-assessment scoring systems in quantifying individual’s risk for developing type 2 diabetes mellitus (T2DM). Thus, a simple risk-assessment scoring system for early screening of T2DM among Bangladeshi adults would be beneficial to identify the high-risk adults and thus taking adequate preventive measures in combating DM. Objective: The purpose of the study was to calculate the risk assessment score for developing type 2 DM among Bangladeshi adults using IDRS (Indian Diabetes Risk Score) tool and to assess the association of different risk factors of IDRS tool with the risk score. Materials and method: The cross sectional observational study was conducted among randomly sampled 482 adult Bangladeshi male and female subjects. The study population consisted of non-diabetic adults visiting the outpatient department (OPD) of Medicine, MARKS Medical College & Hospital, a tertiary care hospital in Dhaka, Bangladesh, from June 2018 to May 2019. A Semi-structured questionnaire consisting of demographic characteristics, risk factor profile of Indian Diabetes Risk Score (IDRS) was used. All the participants were assessed and categorized as high (IDRS ≥60), moderate (IDRS 30-50) and low risk (IDRS